Let's have another cup of green tea! - Benno F. Zimmermann; Lilli Drees (Heliyon)
For this study, the content of the main flavanols, theanine and caffeine in 17 samples of loose leaf green tea were analyzed regarding the leaves as well as the first and second infusions. The infusion conditions followed the instructions on the labels as consumers are supposed to do. The leaf green teas were infused twice and the infusions were examined separately. The galloylated flavanols, i.e., epicatechin gallate and epigallocatechin gallate, were found in roughly equal concentrations in the first and second infusions (medians of 96 % and 106 %, respectively, relative to the first infusion). The non-galloylated flavanols, i.e., epigallocatechin and epicatechin, and caffeine had mostly lower concentrations in the second infusion down to two thirds compared to the first infusion (medians of 72 %, 73 % and 83 %, respectively). Theanine is always higher in the first infusion, in some cases two times higher (median of 58 %). This correlates with the polarity of the compounds. It can be concluded that the second infusion of leaf green tea still contains considerable amounts of caffeine, theanine and flavanols.